Character Education Learning Strategies in Developing Students’ Literacy Skills - Hendrik, Maikel (International Journal of Multidisciplinary Sciences, 2024)
The research aimed to describe character education learning strategies in developing students’ literacy skills. The method used in this research was descriptive qualitative, where most of the data came from literature studies. The lack of interest in reading books (literacy) and critical thinking skills among students is one of the obstacles in Indonesia’s education world nowadays. It is based on the fact that some students who lack interest in reading cannot think critically in processing and obtaining reliable and actionable information. Therefore, efforts, strategies, and methods used in learning are needed to foster students’ ability and interest in reading so that students can have the ability to think critically in processing the information obtained in the hope of creating a golden generation that can compete in this era.